The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/pc.25486
|View full text |Cite
|
Sign up to set email alerts
|

Production of polyacrylonitrile/boehmite nanofibrous composite tubular structures by opposite‐charge electrospinning with enhanced properties from a low‐concentration polymer solution

Abstract: Polyacrylonitrile (PAN)/boehmite nanofibrous composite tubular structures were fabricated from dilute polymer solutions using an opposite‐charge electrospinning method. The samples were characterized by X‐ray diffraction, Differential scanning calorimetry, scanning electron microscopy, Fourier‐transform infrared spectroscopy, fast Fourier transform, and tensile tests. The presence of boehmite nanoparticles in the electrospun PAN nanofibers prevented bead formation, resulting in uniform fibers with smaller diam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…The achievements of current nanofiber technology are one of the most important goals of modern research, which is produced by the electrospinning technique that allows the preparation of non-woven fibrous materials with distinct morphological properties such as fine diameters, high gas permeability [1][2][3][4], small fibrous pore sizes, large surface-to-volume ratio, highly disciplined porosity, and flexibility [5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…The achievements of current nanofiber technology are one of the most important goals of modern research, which is produced by the electrospinning technique that allows the preparation of non-woven fibrous materials with distinct morphological properties such as fine diameters, high gas permeability [1][2][3][4], small fibrous pore sizes, large surface-to-volume ratio, highly disciplined porosity, and flexibility [5][6][7][8] .…”
Section: Introductionmentioning
confidence: 99%
“…However, in some cases an appearance of beads supports an application of nanofibers, as in the case of improving adhesion [ 1 , 2 ]. Bead formation strongly depends on various factors such as voltage [ 9 ], tip-to-collector distance [ 9 ], and additives [ 10 , 11 ]. A choice of solvents also contributes to this phenomenon [ 10 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the recent years, studies on nanofibers have been increasing and studies reported on nanofiber web reinforced glass/epoxy composites have mainly been focused on improvement of their mechanical properties. [26][27][28][29][30][31][32][33][34] However, many novel and light weight acoustical and thermal insulating materials have been introduced in recent years and nanofiber-based materials are promising materials for insulation application and other application areas such as energy storage and energy generators. [32,[35][36][37][38][39][40] Na et al [35] studied on the effect of layers of nanofiber webs on regular fiber knitted fabric on sound absorption.…”
Section: Introductionmentioning
confidence: 99%